Financial Ratio Analysis to Measure Financial Performance at Pt. Aneka Tambang (Persero) Tbk. - Nurasyifa, Ratu Safira; Alwi, Alwi; Nurhayati, Nurhayati (Devitara Innovations, 2024)
The purpose of this study is to analyze and find out how much financial performance PT. In measuring the company's financial performance, the data analysis technique used is financial ratio analysis which includes 1). Liquidity (Current ratio) 2). Solvency (debt to assets ratio) 3). Activity (Total asset turnover) and 4). Profitability (Return on equity). By using the One Sample T-test with the help of the SPSS Version 26 program. The sample used in this study is financial statements in the form of data on sales, current debt, total debt and net profit for the last 10 consecutive years from 2013 to 2022. Based on the results of research and analysis, it shows that 1). The financial performance of PT. Aneka Tambang (Persero) Tbk during 2013-2022 reviewed from the liquidity ratio (Current ratio) the results of the study show that the indicator is not performing well. 2). Solvency (debt to asset ratio), the results of the study show that the indicator is not performing well. 3). Activities (Total asset turnover), the results of the financial performance research of PT. Aneka Tambang (Persero) Tbk, which is considered not good. 4). The results of the calculation of the Profitability ratio (Return on equity) show that the financial performance of PT. Aneka Tambang (Persero) Tbk, from this indicator, is also considered to be performing poorly.